Validation of the Lewis score for the evaluation of small-bowel Crohn’s disease activity - Cotter, José; Dias de Castro, Francisca; Magalhães, Joana; Moreira, Maria João; Rosa, Bruno (Endoscopy, 2015)
Background and study aims: The Lewis score was developed to measure mucosal inflammatory activity as detected by small-bowel capsule endoscopy (SBCE). The aim of the current study was to validate the Lewis score by assessing interobserver correlation and level of agreement in a clinical setting.Patients and methods: This was a retrospective, single-center, double-blind study including patients with isolated small-bowel Crohn’s disease who underwent SBCE. The Lewis score was calculated using a software application, based on the characteristics of villous edema, ulcers, and stenoses. The Lewis score was independently calculated by one of three investigators and by a central reader (gold standard). Interobserver agreement was assessed using intraclass correlation (ICC) coefficient and Bland – Altman plots.Results: A total of 70 patients were consecutively included (mean age 33.9 ± 11.7 years). The mean Lewis score was 1265 and 1320 for investigators and the central reader, respectively. There was a high correlation, both for scores obtained for each tertile (first tertile r = 0.659 – 0.950, second tertile r = 0.756 – 0.906, third tertile r = 0.750 – 0.939), and for the global score (r = 0.745 – 0.928) (P < 0.0001). Interobserver agreement was almost perfect between the investigators and the central reader (first tertile ICC = 0.788 – 0.971, second tertile ICC = 0.824 – 0.943, third tertile ICC = 0.857 – 0.968, global score ICC = 0.852 – 0.960; P < 0.0001). The inflammatory activity was classified as normal (score < 135) in 2.9 % vs. 2.9 %, mild (score ≥ 135 – < 790) in 51.4 % vs. 55.7 %, and moderate to severe (score ≥ 790) in 45.8 % vs. 41.4 % of patients, respectively (P < 0.001).Conclusion: A strong interobserver agreement was demonstrated for the determination of the Lewis score in a practical clinical setting, validating this score for the reporting of small-bowel inflammatory activity. The Lewis score might be used for diagnosing, staging, follow-up, and therapeutic assessment of patients with isolated small-bowel Crohn’s disease.